Analisis ISAK 35 Tentang Penyajian Laporan Keuangan Pada Yayasan Save The Children Indonesia - Lany Nova Putong; Inaya Nur Anisa; Jesicca Lusyanawati; Ade Sri Mulyani (Universitas Warmadewa, 2025)
This research aims to analyze ISAK 35 on financial statements and to determine the preparation, form and content of reports on Save the children Indonesia Foundation. This research method uses qualitative descriptive analysis. The data used in this research is secondary data in the form of the annual financial statements of the Save the children Foundation in 2020 and 2021. Based in the results of the study, the financial statements of the save the children foundation have not yet implemented ISAK No.35 in the foundation’s financial statements, there is only a statements of financial position, a statement of activities and a cash flow statement, there is no statement of changes in net assets and notes to financial statements (CALK) and there are differences in the term “statement of activities” which should “be statement of comprehensive income” in accordance with the provisions of ISAK No.35. After designing the statement of changes in net assets in accordance with the provisions of ISAK No.35, it is known that the final balance of unrestricted net assets in 2021 is IDR 45,753,509,736 and in 2020 it is IDR 32,622,342,019